Upaya Peningkatan Kompetensi Guru dalam Pengelolaan Kegiatan Belajar Mengajar di Masa Pandemi Covid-19 melalui Supervisi Akademik dengan Pendekatan Kolaboratif - Ida Susanti (Asatiza: Jurnal Pendidikan, 2021)
Collaborative supervision is partnership-based supervision between the supervisor and the supervisee. The purpose of this research was to find out whether academic supervision through a collaborative approach can improve teacher competence in managing teaching and learning activities and how teachers' responses to the learning in the Even Semester 2020/2021 at SMA Negeri 2 Bunguran Timur. This research method was classroom action research with two cycles. The results showed that academic supervision through a collaborative approach could scientifically improve teachers' competencies in the Management of Teaching and Learning Activities, as evidenced by the increase of supervision percentage from the aspect of academic supervision that met all of the criteria from 31% to 83% after the action. The teachers responded positively to the academic supervision using a collaborative approach, which can help them in teaching and learning activities.